Incorporation of screwless press-fit acetabular cups and disappearance of polar gaps - Agarwala, Sanjay (J Clin Orthop Trauma, 2020)
BACKGROUND: Uncemented press-fit acetabular cups without screws rely on the elastic recoil of the bone for its primary stability and tend to leave polar gaps with its use. The clinical significance of these gaps and the functional outcome of the patients with polar gaps is evaluated in this study. METHODS: This comparative analysis was done on 224 cementless primary THA using Deltamotion® Hip System from January 2010 to December 2017. Patients were divided into two groups based on the presence or absence of polar gaps on immediate post-operative radiographs. Patients were observed for their clinical, radiological and functional outcomes with regular follow ups. At each follow-up, patients’ clinical outcome was evaluated using the Harris Hip Score (HHS) and Patient Reported Outcome Measures (PROMs). RESULTS: 14 of 224 patients(6.25%) demonstrated polar gaps in their immediate post-operative radiographs. No statistically significant difference was noted in the final mean HHS between the two groups. The polar gaps ranged from 0.5 to 1.8 mm (mean-1.09 mm). None of the patients showed progression of the polar gaps. All patients showed bony ingrowth into the gaps at a mean of 8.57 months. CONCLUSION: The presence of polar gaps in the immediate post-operative radiographs are not of a major clinical significance provided a secure peripheral fit is achieved intra-operatively. The functional outcome and rehabilitation in such patients is at par with that seen in the patients without polar gaps. Disappearance of these polar gaps is a rule rather than an exception.